Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.9 - Linearization and Differentials - Exercises 3.9 - Page 175: 32



Work Step by Step

We have: $y=cot^{-1} \sqrt{t-1}=cot^{-1}(t-1)^{1/2}$ Derive: $\frac{dy}{dt}=\frac{(\frac{1}{2}(t-1)^{-1/2})}{1+[(t-1)^{1/2}]^{2}}$ =$\frac{-1}{2\sqrt{t-1}(1+t-1)}$ =$\frac{-1}{2t\sqrt{t-1}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.